Rhodium-Catalyzed Asymmetric Amination of Allylic Trichloroacetimidates - Arnold, Jeffrey S.; Nguyen, Hien M. (Synthesis, 2013)
A summary is presented of dynamic kinetic asymmetric transformations of racemic allylic trichloroacetimidates in the presence of chiral diene-ligated rhodium catalysts. The reaction is applicable to a wide variety of secondary and tertiary trichloroacetimidates containing aniline or benzylamine nucleophiles, affording nitrogen-containing tertiary and quaternary centers in good yields and with high levels of regio- and enantioselectivity. This catalytic method addresses many of the limitations previously associated with syntheses of these compounds.
Keywords: asymmetric catalysis; aminations; rhodium; catalysis; imidates